The Take Control Course: Conceptual Rationale for the Development of a Transdiagnostic Group for Common Mental Health Problems - Morris, Lydia; Mansell, Warren; McEvoy, Phil (Frontiers in Psychology, 2016)
Background: Increasingly, research supports the utility of a transdiagnostic understanding of psychopathology. However, there is no consensus regarding the theoretical approach that best explains this. Transdiagnostic interventions can offer service delivery advantages; this is explored in the current review, focusing on group modalities and primary care settings. Objective: This review seeks to explore whether a Perceptual Control Theory (PCT) explanation of psychopathology across disorders is a valid one. Further, this review illustrates the process of developing a novel transdiagnostic intervention (Take Control Course; TCC) from a PCT theory of functioning. Method: Narrative review. Results and Conclusions: Considerable evidence supports key tenets of PCT. Further, PCT offers a novel perspective regarding the mechanisms by which a number of familiar techniques, such as exposure and awareness, are effective. However, additional research is required to directly test the relative contribution of some PCT mechanisms predicted to underlie psychopathology. Directions for future research are considered.